2013
DOI: 10.1002/pds.3407
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an algorithm to estimate gestational age in electronic health plan databases

Abstract: Purpose To validate an algorithm that uses delivery date and diagnosis codes to define gestational age at birth in electronic health plan databases. Methods Using data from 225,384 live born deliveries among women aged 15–45 years in 2001–2007 within 8 of the 11 health plans participating in the Medication Exposure in Pregnancy Risk Evaluation Program, we compared 1) the algorithm-derived gestational age versus the “gold-standard” gestational age obtained from the infant birth certificate files; and 2) the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 31 publications
0
91
0
Order By: Relevance
“…Using the birth certificate data to calculate the LMP has been validated previously by one of the participating health plans, which found a concordance of +/- 2 weeks in the LMP between the birth certificate and the medical records in 94% of the records reviewed(12). In addition, another recent validation study(13) found that LMP-based gestational age and obstetric estimate-based gestational age were identical in more than half of all deliveries and within ±1 week in approximately 85% of all deliveries; the difference in means was 1 day.…”
Section: Methodsmentioning
confidence: 98%
“…Using the birth certificate data to calculate the LMP has been validated previously by one of the participating health plans, which found a concordance of +/- 2 weeks in the LMP between the birth certificate and the medical records in 94% of the records reviewed(12). In addition, another recent validation study(13) found that LMP-based gestational age and obstetric estimate-based gestational age were identical in more than half of all deliveries and within ±1 week in approximately 85% of all deliveries; the difference in means was 1 day.…”
Section: Methodsmentioning
confidence: 98%
“…We estimated gestational age at delivery by imputing standard ages based on delivery prematurity or post-term delivery diagnoses codes from the mother and linked child. [2224] To capture complete prenatal and postpartum immunization and clinical information, we required continuous health plan enrollment from the estimated onset of pregnancy to seven days post-delivery (Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…11, 12 However, the sensitivity is much lower (between 45% and 80%) and is particularly low for infants born at 35 or 36 weeks’ gestation. 12, 13 Consequently, only a subset of infants born preterm are coded as preterm.…”
Section: Methodsmentioning
confidence: 99%